Den familiære relasjonens betydning for pårørendes behov i møte med helsetjenesten - Hanssen, Helene; Sommerseth, Rita (Nordisk tidsskrift for helseforskning, 2015)
The Significance of Family relations to Informal Carers’ Needs in interaction with Health ServicesThis article is based on a study aiming to explore informal carers’ needs and experiences in their contact with health services. The study was accomplished in 2011 and consisted of two sub-studies: a survey addressing informal carers in general and a focus-group study, where the participants were informal carers to one or more family members. In this article, the qualitative data from both studies are emphasised: the open written statements in the questionnaires and the focus-group interviews. The results show a similarity in informal carers’ needs and experiences independent of the patients’ diagnoses. However, we find that the needs are related to the family relation between the informal carer and patient. Particularly, there is a difference between the needs of those who are informal carers to their partner and those who care for their own parent(s) or grown children. The value of informal carers’ support also is clearly pointed out in the results. Our findings highlight the importance of professional health workers paying attention to both the informal carer and the patient, individually as well as relationally.
Keywords: Informal carer; caregiver; support; family relation; health services; health workers; pårørende; prørendestøtte; familierelasjon; helsetjeneste; helsepersonell